Fitnah Dalam Al-Qur’an: Telaah Terhadap Penafsiran Ibnu Katsir - Parwanto, Parwanto; Romadlon, Arif Firdausi Nur; Bagaskara, Dzulfikar Tri; Pratama, Rizky (PT. Riset Press International, 2024)
The main problem examined in this study is the interpretation of the word fitnah which most people misinterpret, while researchers will use the book of Ibn Kathir's interpretation in examining the word fitnah. This study aims to find out what the meaning of fitnah mentioned in the Qur'an according to Ibn Kathir and also to find out how the impact of the fitnah. This research is a type of Library Research or library review using a thematic or maudhu'i approach. The results of this study indicate the meaning of the word Fitnah Ibn Kathir is Shirk, tests and trials, tests, trials, excuses, returning to disbelief, doubts, disasters, adzab, mixing between truth and falsehood, torment, apostasy, doubt, kufr and hypocrisy, kufr, hypocrisy and heresy. Meanwhile, the effects of the fitnah are falling into witchcraft, causing people to go astray, jealousy, blindness and deafness from the truth, disbelief or gratitude for blessings, wars, destruction among mankind, the impact of obeying or disobeying, and feeling in the truth.